2023
DOI: 10.1093/jambio/lxad204
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria intrinsic to Medicago sativa (alfalfa) reduce Salmonella enterica growth in planta

Jacob D Vitt,
Eleanore G Hansen,
Raghav Garg
et al.

Abstract: Aims The purpose of this study was to determine whether plant-associated bacteria (PAB) can reduce Salmonella enterica colonization and infection of alfalfa sprouts to reduce the risk of foodborne illness. Methods We isolated plant associated bacteria from alfalfa seeds and sprouts. Monoclonal isolates of the bacteria were obtained and tested for their ability to inhibit Salmonella Typhimurium growth in alfalfa sprouts over 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 85 publications
0
0
0
Order By: Relevance
“…Our results are in line with previous reports, which showed inhibition of S. enterica on sprouted seeds by nonspore-forming bacteria. For example, Vitt et al (2023) recently reported that plant-associated bacteria, including members of the Pseudomona and Pantoea genera, reduced Salmonella growth in alfalfa sprouts from ca. 10 8 to ca.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are in line with previous reports, which showed inhibition of S. enterica on sprouted seeds by nonspore-forming bacteria. For example, Vitt et al (2023) recently reported that plant-associated bacteria, including members of the Pseudomona and Pantoea genera, reduced Salmonella growth in alfalfa sprouts from ca. 10 8 to ca.…”
Section: Discussionmentioning
confidence: 99%
“…10 8 to ca. 10 5 CFU/g (Vitt et al, 2023). Liu and co-workers found that P. fluorescenes A506, a known biocontrol agent, inhibited the attachment of S. enterica and enterohemorrhagic E. coli strains to alfalfa seeds, as well as other vegetable seeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation